2008
DOI: 10.4012/dmj.27.340
|View full text |Cite
|
Sign up to set email alerts
|

Type I Collagen Grafting on Titanium Surfaces Using Low-temperature Glow Discharge

Abstract: To improve the bioactivity of titanium surfaces, glow discharge was used to facilitate collagen grafting on titanium disks. Titanium test specimens were pre-treated by glow discharge fed with a mixture of argon and allylamine (AA) gases. Treated titanium disks were then grafted with type I collagen using glutaraldehyde (GA) as a crosslinking agent. The surfaces of collagen-grafted titanium disks were evaluated using scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) and X-ray photoelectron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
(28 reference statements)
1
22
0
1
Order By: Relevance
“…It is an especially efficient tool for surface treatment of biodegradable polymers, due to its non-destructive property [25]. Several studies indicate that GDP not only can be used for cleaning and chemical modification [2,4,7,18,25], but can also be used for creating a number of biofunctional groups and increasing surface wettability [7,18] which is helpful to improve the biocompatibility of biomaterials [3,10,22]. GDP treatment is also used for surface treatment of titanium/titanium alloys [11,20] due to its highly efficient cleaning and disinfection properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an especially efficient tool for surface treatment of biodegradable polymers, due to its non-destructive property [25]. Several studies indicate that GDP not only can be used for cleaning and chemical modification [2,4,7,18,25], but can also be used for creating a number of biofunctional groups and increasing surface wettability [7,18] which is helpful to improve the biocompatibility of biomaterials [3,10,22]. GDP treatment is also used for surface treatment of titanium/titanium alloys [11,20] due to its highly efficient cleaning and disinfection properties.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance biocompatibility on titanium surfaces, GDP technology can be used to graft various extracellular matrix proteins to the titanium surface, including type I collagen and fibronectin [3,13,27]. To resist platelet aggregation and subsequent blood coagulation on polymer-based biomaterials, albumin grafting was proposed by several scholars [8,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another example is plasma thermal spraying 10) , in which a Ti plate was plasma sprayed by the glow discharge in allylamine gas, followed by consecutive immersion in glutaraldehyde and type I collagen solutions. An example of the electrodeposition method involved the immersion of a Ti plate in a saline solution of polyethylene glycol (PEG) with an NH 2 group at its end to electrodeposit PEG 11) .…”
Section: Methods For the Biofunctionalization Of The Ti Surface And Tmentioning
confidence: 99%
“…While titanium (Ti) and its alloys are highly biocompatible (bioinert) materials with excellent mechanical properties, additional surface modification is necessary to achieve higher biofunctionality, such as specific cell attachment ability. This can often be realized using methods such as silanization [1][2][3][4][5][6] , tresyl chloride activation 7) , sol/gel 8) , plasma spray 9,10) , and electrodeposition 11) . While Ti implants have recently become the most common choice for dental implant treatment, they have an essential drawback as a natural dental root replacement in that they lack periodontal membrane functions such as sensing and absorption of externally applied forces or the protection of the periodontal tissue from infection by epithelial attachment.…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen production increases with modification by ethane-1,1,2- triphosphonic acid and methylenediphosphonic acid grafted onto Ti [47]. Type I collagen is grafted with glutaraldehyde as a cross-linking agent [48]. For the electrodeposition, it is found that an alternating current (AC) between À1 and +1 V vs. SCE with 1 Hz is more effective than direct current (DC) to immobilize type I collagen to Ti and durability in water is high [49] as shown in Fig.…”
Section: Proteins and Collagenmentioning
confidence: 99%